Dreams of finding money: four German surveys from 1956 to 2000 - Schredl, Michael (International journal of dream research, 2023)
Money plays an important role in our everyday life; thus, the question arises how often money play a role in our dreams. So far, only the topic of finding money in dreams have been studied systematically. In four representative surveys from 1956 to 2000 carried out in Germany, about 16% of the participants (overall N = 4,613) reported having had “finding money” dreams in the last few months. In line with previous research, this dream topic was more often reported by men compared to women. Adding the findings that the percentage of “finding money” dreams increased from 1956 to 2000 and that more younger persons reported these dreams compared to older persons, the findings support the idea that - according to the continuity hypothesis of dreaming - dreams of finding money reflect the importance of financial issues in the dreamer’s waking life. However, more detailed studies are needed to corroborate the findings and underlying theories.
Gesehen am 02.05.2023